High postoperative serum levels of surfactant type B as novel prognostic markers for congenital heart surgery - Is?k,Onur (2014)
Objective: Congenital heart diseases are observed in 5 to 8 of every 1000 live births. The presence of a valuable biomarker during the surgical periods may aid the clinician in a more accurate prognosis during treatment. Methods: For this reason, surfactant protein B plasma levels may help to evaluate patients with cardiac problems diminishing the alveolocapillary membrane stability. In this study, plasma levels of this biomarker were measured in the preoperative and postoperative periods. This study was conducted to detect the differences between pulmonary hypertensive and normotensive patients. The differences before and after cardiopulmonary bypass were examined. Results: The differences in cardiopulmonary bypass time, cross-clamp time , inotropic support dose, and duration of intensive care of patients with and without pulmonary hypertensive were found to be statistically significant (P<0.05). The results revealed that this pathophysiological state was related to other variables that were studied. We believe that the differences in preoperative and postoperative SPB levels could be attributed to alveolocapillary membrane damage and alveolar surfactant dysfunction. We found that this pathophysiological condition was significantly associated with postoperative parameters. Conclusion: The findings of the current study showed that surfactant protein B was present in the blood of patients with a congenital heart disease during the preoperative period. Long by-pass times may exert damage to the alveolocapillary membrane in patients with pulmonary hypertension and preoperative heart failure, and it is recommended to keep the option of surfactant therapy in mind during the postoperative course at the intensive care unit before preparing the patients for extubation.